Evaluation of One Hundred Pediatric Muscle Biopsies During A 2-Year Period in Mofid Children And Toos Hospitals - NILIPOR, Yalda; SHARIATMADARI, Fakhreddin; ABDOLLAH GORJI, Fatemeh; ROUZROKH, Mohsen; GHOFRANI, Mohammad; KARIMZADEH, Parvaneh; TAGHDIRI, Moahammad Mehdi; DELAVARKASMAEI, Hosein; AHMADABADI, Farzad; BAKHSHANDEH BALI, Mohamad Kazem; et al. (Iranian Journal of Child Neurology, 2013)
How to Cite This Article:Nilipor Y, Shariatmadari F, Abdollah gorji F, Rouzrokh M, Ghofrani M, Karimzadeh P, Taghdiri MM, Delavarkasmaei H, Ahmadabadi F, Bakhshandeh bali MK, Nemati H, Saket S, Jafari N, Yaghini O, Tonekaboni SH. Evaluation of One Hundred Pediatric Muscle Biopsies During A 2-Year Period in Mofid Children And Toos Hospitals. Iran J Child Neurol. 2013 Spring;7(2):17-21. Objective Muscle biopsy is a very important diagnostic test in the investigation of a child with suspected neuromuscular disorder. The goal of this study was to review and evaluate pediatric muscle biopsies during a 2-year period with focus on histopathology diagnosis and correlations with other paraclinic studies. Materials & Methods We investigated 100 muscle biopsies belonging to patients with clinical impression of neuromuscular disorder. These patients have been visited consecutively by pediatric neurologists during 2010 to 2012. Samples were investigated by standard enzyme histochemical and immunohistochemical techniques. Result Sixty-nine (69%) males and 39 (39%) females with a mean age of 5.7 years were evaluated. Major pathologic diagnoses were Muscular dystrophy (48 cases), Neurogenic atrophy (18 cases), nonspecific myopathic atrophy (12cases), congenital myopathy (6 cases), storage myopathies (4 cases) and in 6 cases there was no specific histochemical pathologic finding. EMG was abnormal in 79 cases. Degree of correlation between EMG and biopsy result was significant in children ≥ 2 years of age. Conclusion This study confirms the high diagnostic yields of muscle biopsy especially only if standard and new techniques such as enzyme study and immunohistochemistry are implemented. Also, we report 11 cases of Merosin negative congenital muscular dystrophy. This is the largest documented case series of Merosin deficient congenital muscular dystrophy reported from Iran. References 1. Harvey B. Sarnat. Evaluation and Investigation. In:Kliegman. Stanton.Schor. Behrman.Nelson Text Book of Pediatrics.19th edition.Philadelphia: Elsevier,2011. P.2109-2112. 2. Harvey B. Sarnat and John H Menkes. Disease of The Motore Unit. In: John H Menkes, Harvey B Sarnat, Bernard L Maria. Child Neurology. 7th edition.california: lippincott,2006.p.969-972. 3. Marius Kuras Skram, Sasha Gulati, Erik Larrson. Muscle Biopsies In Children-An Evaluation Of Histopathology And Clinical Valueduring A 5-Year Period. Upsala J Med Sci 2009 March:114 (1);41-45. 4. Owji M, Modaressi F. Diagnosis of Myopathies Using Histology. Histochemistry, Immunohistochemistry and Electron Microscopy 2010,12 (4):434 -440. 5. Dua T, Das M, Kabra M. Spectrum of Floppy Children in Indian Scenario. Indian Pediatric J 2001, 38:1236-1243. 6. Rabie M, Jossiphov J, Nevo Y. Electromyography accuracy compared to muscle biopsy in childhood. J Child Neurol 2007 jul; 22(7):803.8.